2014
DOI: 10.5812/archcid.18062
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Satisfaction With Tuberculosis Services of Directly Observed Therapy Programs in the Gezira State of Sudan

Abstract: Nowadays it has been proven that multidrug resistant and C. difficile infections have enjoyed virulent nature (1), thus, establishing policies on the duration of contact precaution to safety care for patients and prevent spread of these bacteria should be considered (2). Recently, the society for health care epidemiology of America (SHEA) has published a guidelines, which precisely included all dimension and time of contact precaution (3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
2
6
1
Order By: Relevance
“…Therefore, this has resulted into urban biasness in the health care system. Similar findings were reported by Mohamed, et al [ 24 ], who reported that in Sudan, 66% from urban patients and 48.9% from rural patients were satisfied with their TB treatment facilities.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, this has resulted into urban biasness in the health care system. Similar findings were reported by Mohamed, et al [ 24 ], who reported that in Sudan, 66% from urban patients and 48.9% from rural patients were satisfied with their TB treatment facilities.…”
Section: Discussionsupporting
confidence: 90%
“…Patients’ satisfaction is based on perceived health care services of individual patients, which is influenced by the level of care provided by the health system [ 24 ]. It is often based on patients’ expectations from the health care and self-assessment of their experiences.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding is similar previous findings which reported that TB patients who had no income were more satisfied with the TB care service than those who had savings [20]. Unlike our findings and those from other studies [21,22], the authors reported a positive relationship between service satisfaction and educational level. This scenario may be due to people from lower social classes having modest expectations, partly due to limited awareness or limited ability to choose and hence vary expectation.…”
Section: Discussioncontrasting
confidence: 56%